Can Optimal Digital Innovation and Financial Inclusion Drive Poverty Reduction in the Niger Delta Region of Nigeria? - Ifere, Eugene Okoi; Okosu, Napoleon David (International Journal of Economics and Financial Issues, 2017)
Poverty has remained a stubborn challenge in the Niger Delta Region of Nigeria amidst abundant natural resources. The sheer complexity of the Niger Delta with coastal waterways, creeks and islands creates unique challenges that cannot be underestimated. The study surveyed the extent of poverty using monthly income distribution, and degree of financial inclusion using access and usage of products and services. Findings revealed that women are more financially excluded. Findings also showed that majority of the population are unbanked and highly discouraged using financial products and services especially ATM for fear of debiting without payment, long queues, high interest rates on loans and difficulty in accessing credit from financial institutions. The study suggests that the provisions of optimal digital financial services and products in this rural community with adequate education and advocacy for all the population will broaden financial inclusion, thereby contributing to poverty reduction. Keywords: Financial inclusion, poverty, digital innovation JEL Classifications: G21, O4